2022
DOI: 10.1002/mrm.29153
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and multispectral DWI near metallic implants using a non‐linear phase Carr‐Purcell‐Meiboom‐Gill diffusion preparation

Abstract: Purpose DWI near metal implants has not been widely explored due to substantial challenges associated with through‐slice and in‐plane distortions, the increased encoding requirement of different spectral bins, and limited SNR. There is no widely adopted clinical protocol for DWI near metal since the commonly used EPI trajectory fails completely due to distortion from extreme off‐resonance ranging from 2 to 20 kHz. We present a sequence that achieves DWI near metal with moderate b‐values (400–500 s/mm2) and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Koch et al provided the first demonstration of MSI principles in DW-MRI (16), leveraging a fusion of 2D-MSI (17) and split-blade (18) Periodically Rotated Overlapping ParallEL Lines with Enhanced Reconstruction (PROPELLER) (19) DW techniques (20). More recently, Lee et al (21) proposed a 3D-MSI approach by developing carefully matched MSI-specific radiofrequency pulses for diffusion sensitization. In the present report, we utilize the 2D approach of Koch et al ( 16), which has recently been demonstrated in preliminary applications for spinal cord imaging (22), assessment of soft tissue pathology near total hip replacements (23), and quantitatively assessed utilizing standardized phantoms (24).…”
mentioning
confidence: 99%
“…Koch et al provided the first demonstration of MSI principles in DW-MRI (16), leveraging a fusion of 2D-MSI (17) and split-blade (18) Periodically Rotated Overlapping ParallEL Lines with Enhanced Reconstruction (PROPELLER) (19) DW techniques (20). More recently, Lee et al (21) proposed a 3D-MSI approach by developing carefully matched MSI-specific radiofrequency pulses for diffusion sensitization. In the present report, we utilize the 2D approach of Koch et al ( 16), which has recently been demonstrated in preliminary applications for spinal cord imaging (22), assessment of soft tissue pathology near total hip replacements (23), and quantitatively assessed utilizing standardized phantoms (24).…”
mentioning
confidence: 99%